KARATE IN OLD AGE: A NEW POSSIBILITY (Fiep Bulletin - online, 2013)
The purpose of this project was to provide physical activities to the elderly with the objective of improving their functional ability, preventing and assisting in the treatment of pathologies, strengthening disposition, ability and confidence to deal with everyday life. This research has characterized itself in a qualitative, descriptive and interpretative approach, in which the collaborators were elderly people with ages from 61 to 79 years old. The field of study selected was Centro Universitário Feevale (Campus I) from Novo Hamburgo, RS. Adapting technical moves from Karate, so that it could be practiced by elderly, demanded an activities program, in which aims and contents would gather the basic requirements to reflect it in an improvement of elderly people's physical and intellectual ability. The proposed activities weren't limited pure and simply to repetition and mechanization of techniques, but exercises and games that made the collaborator pay attention to and memorize a series of movements , to learn some rules and adapt movement according to situation. The results obtained from this research project indicate that practicing karate, even after seventy, can be an excellent way of counterbalancing the decline of diverse functions and organs, moderating aging within the physical, psychological and social spheres.
Keywords: People in old age; Karatê; Quality of life